Admissibilidade da ação rescisória fundada em violação a literal disposição de lei (art. 485,V,CPC) - Maia, Izabelle Albuquerque Costa (2005)
This dissertation s scope has in view to develop a study about the lawsuit referred in the article 485, V, of the Brazilian Procedural Codification (in Portuguese, this codification is named Código de Processo Civil, or CPC), indicated to obstruct a decision that violates the law. The approach chosen drives the dissertation to the study about (i) the general points (lawsuit conditions, procedural requests) and (ii) the specific points (a court decision that doesn t admits revision, term to propose the lawsuit and others legal hypothesis) asked to propose the lawsuit based on the article 485 of the CPC and, more specifically, based on the article 485, V, of the CPC (lawsuit appropriated to rescind a court decision that contains a law violation). According to this planning, deserves approach the lawsuit based on the article 485 as a common lawsuit, with requests legally established in the procedural legislation, and also are studied some general aspects concerning to the procedural admission such as legitimacy, legal competence and the capacity to suspend the execution of the illegal decision. Also deserves attention the exceptional character of the lawsuit based on the article 485, V, of the CPC, considering that its object is to attack a jurisdictional decision that can not be changed by the regular ways (appellation, for instance). The dissertation concludes indicating an amplified interpretation about the article 485, V, of the CPC, approaching all the law violations mentioned in the Brazilian legislation, in order to give priority to the concept of Justice in comparison with the concept of security, specially in situations in which a decision contains a substantial law violation.